A 3D digital analysis of the hard palate wound healing after free gingival graft harvest - Marques, Tiago (2022)
Purpose: Within this context, this pilot study aimed to evaluate the healing dynamics process of the hard palate after free gingival graft harvesting in the short term (3 months), utilizing digital imaging technology and tridimensional analysis software. Furthermore, assessing the results found to verify the existence of a relationship between gender or age with tissue loss. Materials and Methods: For connective-tissue harvesting, fifteen patients with gingival recessions type (RT) 1 and RT2 were selected. On the surgery day (before the procedure) and after three months, palatal impressions were taken in all patients, and cast models were done for posterior model scanning. The following variables were analyzed: mean thickness alterations (x¯ TA), maximum thickness loss (MTL), mean maximum thickness loss (x¯ MTL), and volume alterations (VA). A descriptive and bivariate analysis of the data was done. The data were submitted for statistical evaluation and were significant if p < 0.05. Results: Fifteen patients were analyzed, 11 females (73.3%) and four males (26.7%). The patients’ average age was 28 ± 8.52 years (ranging between 16 and 48 years old). The palatal wound region’s mean thickness and volume changes were −0.26 mm (±0.31) and 46.99 mm3 (±47.47 mm3) at three months. There was no statistically significant result correlating age/gender with any variable evaluated. Conclusions: Connective tissue graft harvesting promoted changes with a standard volume and thickness loss of palatal soft tissue. A 3D digital evaluation was a non-invasive method with a reproducible technique for measuring thickness or volume after connective tissue is collected. There was no relationship between age/gender and any variables analyzed.